Mordida cruzada anterior em crianças - Sandim, Fabiane da Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2010)
The anterior crossbite (MCA) is a malocclusion characterized by a negative horizontal trespass. In this context can be classified as being of dental nature, when there is only a change in slope vestibule-lingual; skeletal when related to a discrepancy of bone bases size, i.e., There is a combination of mandibular prognathism, retrusão jaw, where the teeth of a secundary position themselves to skeletal problems. Finally there are the cross-functional bites, related to a previous front jaw offset to a contact premature, taking the patient to two positions mandibular with marked difference between the usual maximum intercuspation and central. Studies show the prevalence of malocclusion in various stages of development of dentition. SILVA FILHO et al. (1990) observed the occurrence of some sort of diversion of occlusion in 88.53% of a sample consisting of 2,416 children studied, aged 7 and 11 years. Including 7.6% MCA. Regarding the etiological factors, these range from premature contacts up growth patterns changed with significant genetic influence. Early diagnosis, still in deciduous teeth, contributes significantly to the treatment of MCA, because it leverages the development phase to modify changes avoiding asymmetric growth, returns the child aesthetics, contributing with their self-esteem. Thus, according to the type of bite cross etiological factor is a related, but the combination of genetic and environmental aspects is always present. Considering the role of General clinical identifying malocclusions in initial periods of development, the objective of this paper is to present a literature review focused on cross bite in children as well as present a clinical case report

A mordida cruzada anterior(MCA) é uma má oclusão caracterizada por um trespasse horizontal negativo. Neste contexto podem ser classificadas como sendo de natureza dentária, quando há apenas uma alteração na inclinação vestíbulo-lingual; esquelética quando relacionada a uma discrepância de tamanho das bases ósseas, ou seja, há uma combinação entre prognatismo mandibular, retrusão maxilar, onde os dentes se posicionam de forma secundária ao problema esquelético. Finalmente existem as mordidas cruzadas funcionais, relacionadas com um deslocamento anterior da mandíbula frente a um contato prematuro, levando o paciente a duas posições mandibulares com diferença marcante entre a máxima intercuspidação habitual e a relação central. Estudos evidenciam a prevalência desta má oclusão em diversos estágios de desenvolvimento da dentição. SILVA FILHO et al(1990) observaram a ocorrência de algum tipo de desvio de oclusão em 88,53% de uma amostra composta por 2.416 crianças estudadas, com idades em 7 e 11 anos. Dentre elas, 7,6 % apresentavam MCA. Quanto aos fatores etiológicos, estes variam desde contatos prematuros até padrões de crescimento alterados com significante influência genética. O diagnóstico precoce, ainda na dentadura decídua, contribui de forma significativa para o tratamento da MCA, pois aproveita a fase de desenvolvimento para modificar as alterações evitando um crescimento assimétrico, devolve estética a criança, contribuindo com a sua auto-estima. Deste modo, de acordo com o tipo de mordida cruzada anterior há um fator etiológico relacionado, porém a combinação entre aspectos ambientais e genéticos sempre está presente. Considerando o papel do clínico geral na identificação de más oclusões em períodos iniciais do desenvolvimento da dentição, o objetivo deste trabalho...
Keywords: Má oclusão; Diagnóstico precoce; Oclusão dentária; Criança; Malocclusion